THU0764-HPR What moves the rheumatologist? unravelling decision making in ssc referral – a qualitative study. (15th June 2017) - Stöcker, JK; Cup, E; Sanden, R Nijhuis-van der; Staal, B; Vonk, M; Hoogen, F van den; Ende, E van den
Abstract : Background: Well-coordinated multidisciplinary non-pharmacological care is considered to be a cornerstone in the management of patients with systemic sclerosis (SSc). However, unmet information and healthcare needs are found to be common in patients with SSc [1]. In addition, referrals by rheumatologists' do not always correspond with potential treatment goals as identified by health professionals (HP)[2]. Objectives: The aim of this study was to gain insight in the perspective of rheumatologists about the referral process of SSc patients to non-pharmacological care and to identify starting points for its optimisation. Methods: Semi structured in-depth interviews were held with 13 out of 24 rheumatologists, specialised in SSc management, from different Dutch university and regional medical centres. The qualitative data analysis used an inductive thematic analysis by moving through a process of coding in layers of abstraction and interpretation: familiarization with data, generating initial codes, grouping similar codes in categories, discussing categories, searching for themes among categories, reviewing themes, defining and naming themes, and producing the final report. Results: One major theme was identified as influencing decision making: "beliefs" and its three sub themes: a) beliefs about one's own professional role; b) beliefs about the patients' ability to take an active role in managing the disease and c) beliefs about the added value of non-pharmacological care. We also found an additional theme reflecting the "needs" of the rheumatologists regarding professional multidisciplinary collaboration (Figure 1 ). Another remarkable finding to be further explored was the discrepancy we found between the reliance of rheumatologists on established routines with regard to when and to whom to refer and the low confidence in HPs competencies on the other hand. Conclusions: The results of our study give insight that rheumatologists base their referral decisions on complex reasoning mindlines and beliefs about their own professional role, the patient's role and HP competencies. References: Willems, L. M., Kwakkenbos, L., Leite, C. C., Thombs, B. D., van den Hoogen, F. J., Maia, A. C., & van den Ende, C. M. (2014). Frequency and impact of disease symptoms experienced by patients with systemic sclerosis from five European countries. Clinical And Experimental Rheumatology, 32(6 Suppl 86), S-88–93. Schouffoer, A., Zirkzee, E., Henquet, S., Caljouw, M., Steup-Beekman, G., Laar, J., & Vlieland, T. (2011). Needs and preferences regarding health care delivery as perceived by patients with systemic sclerosis. Clinical Rheumatology, 30(6), 815–824. doi:10.1007/s10067–010–1645–6. Disclosure of Interest: None declared